Buy Burkinabè! Yam Pukri's Agripol advocacy platform in Burkina Faso - Ouédraogo, Sylvestre; Sawadogo, Théophile Assane (Technical Centre for Agricultural and Rural Cooperation, 2017)
The 2014–15 season was a difficult one for women’s rice-marketing cooperatives in Burkina Faso. Locally grown rice was slightly more expensive than imported grain, and big imports in the previous years meant that small-scale rice farmers and cooperatives were no longer able to sell their grain. Their national association, UNERIZ, was left with over 2,000 tonnes of unsold stock. Growers who had borrowed to invest in production were unable to repay their debts. A change in government policy to prioritise locally grown grain and to deter imports would help. But the Comité Interprofessionnel du Riz du Burkina, the group mandated to lobby on the growers’ behalf, lacked the tools to put pressure on the government. So Agripol, a CTA-supported project run by Yam Pukri, stepped in to help. It used social media to call on people to choose locally grown rice.